Trail of decryption of molecular research on Botryosphaeriaceae in woody plants - K.W. Thilini CHETHANA (Phytopathologia Mediterranea, 2016)
The family Botryosphaeriaceae is species rich and includes pathogens, saprobes and endophytes of economically important agricultural crops and plants. As pathogens, Botryosphaeriaceae species employ evolving defensive and counter-defensive strategies that enable them to infect their hosts. Molecular genetic results showed high genetic variability among Botryosphaeriaceae species, which could be a key determinant to their differing environmental roles on hosts and differences in their virulence. Improved technologies such as whole genome re-sequencing, integrated RNA-Seq, comparative and ab initio approaches for molecular genetics and mutation analysis have revealed possible virulence factors that might be involved in the pathogenicity of these fungi. Several genes involved in the pathogenicity processes of botryosphaeriaceous fungi have been identified and characterized. There are numerous reports on the involvement of phytotoxic metabolites in the pathogenicity of these taxa. Availability of whole genomes, genetic transformation and transcriptome analysis of some botryosphaeriaceous species have contributed towards identifying the biological functions of many genes in a fast and accurate way, enabling these fungi to be used as model organism for molecular research of plant opportunistic fungal pathogens in woody plants. The research on botryosphaeriaceous species will provide understanding of the infection mechanisms, and with designing control strategies against diseases caused by opportunistic fungal pathogens.